Capability of Wild Carob Seeds in Benghazi City, Libya to Germinate and Establish - Aref, Esraa; Eltaguri, Houssein; Alhariry, Khadija; Mukassabi, Tarek (AlQalam Journal of Medical and Applied Sciences, 2025)
This study investigated the germination and growth potential of carob (Ceratonia siliqua L.) seeds collected from three sites in Benghazi City, Libya, under various water regimes and environmental conditions. As a drought-resistant species critical for sustainable agriculture in arid regions, carob faces challenges such as reduced cultivation areas resulting from climate change and poor management. This research evaluated pod and seed attributes at three locations: Quarsha, Sidi Ali, and Tika, and found significant differences among them in pod length, pod weight, number of seeds per pod, and seed weight, with Tika producing the most promising results. Germination tests demonstrated that mechanical scarification significantly enhanced seed germination, while moderate water levels (8–10 ml) proved ideal for seedling growth, particularly in terms of shoot and root development. The study also emphasises the vulnerability of carob seedlings to water stress, noting that root growth was more adversely affected than shoot growth. It can be concluded that site selection and effective water management are crucial to carob growth and establishment success. The study indicates that carob is a tolerant crop species in the extremely arid climate of Libya, advocating for improved irrigation systems, seed treatment methods, and the conservation of genetic resources for sustainable agriculture. Further field trials are suggested to confirm these results in natural settings.